To the statistic theory of dispersion of tensors of electric conductivity and dielectric susceptibility of electrolyte solutions - Odinaev, S.; Ojimamadov, I. (Condensed Matter Physics, 2004)
We have obtained an equation describing space-time behaviour of the current density component by using kinetic equation for one-particle distribution function for the structural units of the solution with the generalized Vlasov potential.
The analytic expression for the complex tensor of electroconductivity σ(ω) is given derived from the Fourier-transform and from the comparison with the differential form of the Ohm’s law. This permitted us to obtain the dielectric susceptibility tensor ε(ω) for conducting media. By identifying the longitudal εk and transversal ε⊥ parts one can determine the anisotropy of the dielectric susceptibility for electrolyte solutions. Отримано рівняння, яке описує просторово-часову поведінку компоненти густини струму, використовуючи кінетичне рівняння для одночастинкової функції розподілу структурних компонент розчину з узагальненим потенціалом Власова. Представлено аналітичний вираз для комплексного тензора електропровідності σ(ω) , який виведений з Фур’є-перетворення і з диференціальної форми закону Ома. Це дало змогу отримати тензор діелектричної сприйнятливості ε(ω) для провідного середовища. Виділяючи поздовжню εk і поперечну ε⊥ частини можна визначити анізотропію діелектричної сприйнятливості для електричних розчинів.